2013
DOI: 10.2147/cia.s52774
|View full text |Cite
|
Sign up to set email alerts
|

Is the Chronic Kidney Disease Epidemiology Collaboration creatinine–cystatin C equation useful for glomerular filtration rate estimation in the elderly?

Abstract: BackgroundWe aimed to evaluate the performance of the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) creatinine–cystatin C equation in a cohort of elderly Chinese participants.Materials and methodsGlomerular filtration rate (GFR) was measured in 431 elderly Chinese participants by the technetium-99m diethylene-triamine-penta-acetic acid (99mTc-DTPA) renal dynamic imaging method, and was calibrated equally to the dual plasma sample 99mTc-DTPA-GFR. Performance of the CKD-EPI creatinine–cystatin C eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Targeted use of cystatin C in this context would offset the increased cost of cystatin C compared to creatinine, a potential consideration when additional testing is ordered. (28, 29)…”
Section: Discussionmentioning
confidence: 99%
“…Targeted use of cystatin C in this context would offset the increased cost of cystatin C compared to creatinine, a potential consideration when additional testing is ordered. (28, 29)…”
Section: Discussionmentioning
confidence: 99%
“…Participants were excluded if they had any of the following: 1) younger than 18 years, or 2) type 1 diabetes, or 3) type 2 diabetes with known non-diabetic renal disease. The other exclusion criteria were described elsewhere [12] . GFR category was classified according to the National Kidney Foundation Disease Outcomes Quality Initiative clinical practice guidelines [13] .…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…The best performance of the CKD-EPI creatinine–cystatin C equation in older people was also confirmed in community-based AGES-Reykjavik Study [ 18 ]. In contrast, in the older Chinese cohort, the bias of the CKD-EPI creatinine–cystatin C equation was greater than with other equations, including short MDRD equation [ 19 ]. Finally, the comparison of CKD-EPI and MDRD formulas in large cohort of nearly 175,000 primary care patients showed that mean bias, although statistically significant at all age groups, diminished with age, from 13% in the 18–29 years age group to − 7.5% in those aged over 90 years [ 20 ].…”
Section: Discussionmentioning
confidence: 99%